Seasonal changes in the gonad morphology of the sea cucumber, Actinopyga lecamora (Jaeger, 1833) in Guimaras, Philippines. - Olaguer, Irish Kathryn Lantin (2010.)
Sea cucmbers are soft bodied echinoderms found in nearly every marine environment, but are most divers in tropicacl shallow-water coral reefs. In terms of reproductive system, holothurians differ from other echinoderms such that they only have a single gonad that consistsof many tubules, which are elongated and branched, and united basally to the dorsal mesentry of the gut. Holothurians are highly exploited echinoderms with fishery largely dependent on wild population. In the Philippines, there is no known investigation on Actinopyga lecanora in literature but this species is highly traded. A knowledge of its reproductive biology is essential in developing culture technology and/or improving fishery management. This study describes the gonad morphology of A. lecanora population in Guimaras. Fixed gonad samples of the DOST - UPV Sea Cucumber Project collected between December 2008 to December 2009 were analyzed in terms of sex, tubule characteristics, mean oocyte number per tubule, oocyte shape and diameter. Gonad maturity were assessed and changes in macroscopic an microscopic characteristics of the gonads along with gonadal index (GI) provided by the Sea cucumber Project were related to seasons of dry-cold, dry-warm and wet seasons. Results revealed that tubule color, size and structure differed with sexual maturity. White-yellowish, short, and thin tubules were immature while orange, bulging, long, and thick ones were mature with mean length and width ranging from 0.67-29.0 mm and 0.19-1.34 mm, respectively. mean number of oocyte in tubule ranged from 1,405-2,526, with mean oocyte diameter of fixed samples ranging from 112.5-262.5 um. Gonadal index peaked in July for female with an absolute fecundity of 4562101 eggs, and in March for the male. The limited number of samples examined especially of males and the alck of histological examination of the gonads prevent a more definitive assessment of the reproductive activity of A. lecanora and calls for further investigation.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Sea cucumber; Actinopyga lecamora